Asuhan Kebidanan pada Kegawatdaruratan Maternal: Studi Literatur tentang Efektivitas Intervensi Kebidanan - Marpaung, Sastrika Handayani (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background: Maternal emergencies are life-threatening conditions during pregnancy, childbirth, and the postpartum period. Prompt and appropriate midwifery intervention can reduce maternal morbidity and mortality. Objective: To analyze the effectiveness of various midwifery interventions in managing maternal emergencies based on a literature review. Methods: This study used a literature review method by reviewing scientific articles published between 2015 and 2025. Searches were conducted through the PubMed, ScienceDirect, Google Scholar, and DOAJ databases using the keywords